Lost in traffic? The K+ channel of lily pollen, LilKT1, is detected at the endomembranes inside yeast cells, tobacco leaves, and lily pollen - Safiarian, Minou J.; Pertl-Obermeyer, Heidi; Lughofer, Peter; Hude, Rene; Bertl, Adam; Obermeyer, Gerhard (Frontiers in Plant Science, 2015)
Fertilization in plants relies on fast growth of pollen tubes through the style tissue towards the ovules. This polarized growth depends on influx of ions and water to increase the tube’s volume. K+ inward rectifying channels were detected in many pollen species, with one identified in Arabidopsis. Here, an Arabidopsis AKT1-like channel (LilKT1) was identified from Lilium longiflorum pollen. Complementation of K+ uptake deficient yeast mutants was only successful when the entire LilKT1 C-terminus was replaced by the AKT1 C-terminus. No signals were observed in the plasma membrane (PM) of pollen tubes after expression of fluorescence-tagged LilKT1 nor were any LilKT1-derived peptides detectable in the pollen PM by mass spectrometry analysis. In contrast, fluorescent LilKT1 partly co-localized with the lily PM H+ ATPase LilHA2 in the PM of tobacco leaf cells, but exhibited a punctual fluorescence pattern and also sub-plasma membrane localization. Thus, incorporation of LilKT1 into the pollen PM seems tighter controlled than in other cells with still unknown trafficking signals in LilKT1’s C-terminus, resulting in channel densities below detection limits. This highly controlled incorporation might have physiological reasons: an uncontrolled number of K+ inward channels in the pollen PM will give an increased water influx due to the raising cytosolic K+ concentration, and finally, causing the tube to burst.